EFFECTIVE MANAGEMENT DECISIONS AS A BASIS FOR SUSTAINABILITY MANAGEMENT TEAM - V. A. Ivanov (Модернизация, инновация, развитие)
Management team functional sustainability is ensured through development and acceptance of effective management decisions. «Sustainability» and «competitiveness» terms are determined, their role and importance are revealed. Overview of scientific approaches and concepts related tothese terms is brought about.